Efficient preconditioning of the linearized Navier-Stokes equations - Silvester, D; Elman, H; Kay, D; Wathen, A (Unspecified, 1999)
We outline a new class of robust and efficient methods for solving subproblems that arise in the linearization and operator splitting of Navier-Stokes equations. We describe a very general strategy for preconditioning that has two basic building blocks; a multigrid V-cycle for the scaler convection-diffusion operator, and a multigrid V-cycle for a pressure Poisson operator. We present numerical experiments illustrating that a simple implementation of our approach leads to an effective and robust solver strategy in that the convergence rate is independent of the grid, robust with respect to the time step, and only deteriorates very slowly as the Reynolds number is increased.